INTERNAL CONTROL OVER FINANCIAL REPORTING - O. Diakonova; M. Davydkina (Вестник университета)
It is considered problems of improving the organization’s internal control over financial reporting. It is also analyzed the procedure of the organization’s internal control over financial reporting, there are considered the main aspects of accounting financial results.